Modern ideas about the causes, pathogenesis and innovative areas of therapy for asthenic syndrome in clinical practice - S. A. Zhivolupov; A. A. Smirnova (Лечащий Врач)
Background. Asthenic syndrome is a morbid condition manifested by increased physical and mental fatigue and exhaustion with mood instability, irritability, sleep disturbance, accompanied by weakening of self-control, impatience, restlessness, intolerance to loud sounds, bright light, strong odours. Clinical manifestations of asthenic syndrome differ from the state of physiological fatigue and overwork in that fatigue or exhaustion arise spontaneously, in the absence of physical or mental effort. In addition, asthenic syndrome is not a physiological phenomenon, is not corrected as a result of rest and requires medical intervention. According to literature data, the frequency of occurrence of asthenic syndrome in the population ranges from 12 to 18%, at the appointment of a general practitioner – from 20 to 25%, in the presence of somatic diseases – from 50 to 100%. The most common tool for diagnosing AS is currently the Multidimensional Fatigue Inventory (MFI-20) questionnaire, and the L. D. Malkova Asthenic Scale is also widely used in the Russian Federation.Results. The review article outlines the relevant problems of the terminology of asthenic syndrome, its classification, location, and statistical coding. Asthenic syndrome is presented as a polyetiological disease, for the prevention of which it is advisable to correct modifiable risk factors for its development. Some mechanisms of the formation of asthenic syndrome as a result of COVID-19 infection are considered, and the common pathogenesis of a number of pathogenetic links of these diseases is emphasized. An innovative direction in the treatment and prevention of asthenic syndrome is modulation of the function of the "gut-brain" axis. For this purpose, the use of a biologically active food supplement containing in its composition the product of meat and bone meal distillation seems to be quite promising.